1998
DOI: 10.1101/lm.4.6.478
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific mRNAs affected by treatments producing long-term facilitation in Aplysia.

Abstract: Neural correlates of long-term sensitization of defensive withdrawal reflexes in Aplysia occur in sensory neurons in the pleural ganglia and can be mimicked by exposure of these neurons to serotonin (5-HT). Studies using inhibitors indicate that transcription is necessary for production of long-term facilitation by 5-HT. Several mRNAs that change in response to 5-HT have been identified, but the molecular events responsible for long-term facilitation have not yet been fully described. To detect additional chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 92 publications
0
9
2
Order By: Relevance
“…In addition, we did not replicate previous findings (Zwartjes et al, 1998) of up-regulation of a reductase-related protein (MFC = 1.02) nor ApCalmodulin (MFC = 1.08). This is not surprising, however, as we analyzed a different timepoint (immediate in prior work versus 1 hour after training in this study) and a different tissue (sensory neurons only in prior work versus entire pleural ganglia in this study).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, we did not replicate previous findings (Zwartjes et al, 1998) of up-regulation of a reductase-related protein (MFC = 1.02) nor ApCalmodulin (MFC = 1.08). This is not surprising, however, as we analyzed a different timepoint (immediate in prior work versus 1 hour after training in this study) and a different tissue (sensory neurons only in prior work versus entire pleural ganglia in this study).…”
Section: Resultscontrasting
confidence: 99%
“…Previous research has shown that long-term sensitization training produces a rapid (within 1 hour) increase in the expression of six different transcripts in the pleural ganglia: ApC/EBP (GenBank: U00994; Alberini, Ghirardi, Metz, & Kandel, 1994), ApCREB1 (GenBank: NM_001256437; Bartsch, Casadio, Karl, Serodio, & Kandel, 1998), ApEgr (GenBank: KC608221; Cyriac et al, 2013), ApTBL-1 (GenBank: U57369; Liu et al, 1997), ApCalmodulin (GenBank: NM_001204580; Zwartjes et al, 1998), and an reductase-related protein (GenBank: NM_001204605; Zwartjes et al, 1998). To date, however, there have been no comprehensive efforts to characterize the rapid transcriptional response to long-term sensitization training (though see Castellucci, Kennedy, Kandel, & Goelet, 1988; Liu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting the expression of either protein was sufficient to block induction of long-term but not short-term facilitation. mRNAs for calmodulin and an as yet unidentified protein were also transiently increased immediately after sensitization training [107]. Three hours after the onset of long-term facilitation increases in the mRNA for the Aplysia homolog of BiP, an endoplasmatic reticulum resident protein with chaperone function, could be detected [108].…”
Section: Memory Formation In Invertebratesmentioning
confidence: 92%
“…In Aplysia, regulating the transcription of several genes is essential for LTF (Noel et al, 1993(Noel et al, , 1994Alberini et al, 1994;Hegde et al, 1997;Zwartjes et al, 1998;Bartsch et al, 2000;Giustetto et al, 2003). Chromatin remodeling plays a crucial role in regulating the expression of ApC/EBP (Guan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%